2011
DOI: 10.1007/s11367-011-0346-y
|View full text |Cite
|
Sign up to set email alerts
|

Water footprint of livestock: comparison of six geographically defined beef production systems

Abstract: Purpose Water use in the livestock sector has featured in the debate about sustainable food systems. Most evidence has come from virtual water calculations which lack impact assessment and adequate consideration of the heterogeneity in livestock production. This study sought new evidence, using a recently developed life cycle impact assessment method for water use to assess six geographically defined beef cattle production systems in New South Wales, Australia, a major production region. Methods The livestock … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
69
2
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(77 citation statements)
references
References 24 publications
(31 reference statements)
3
69
2
2
Order By: Relevance
“…With a similar order to that found in the present study (95 and 217 l/kg LWG), the analysis of six systems for meat production in New South Wales, Australia, by Ridoutt et al (2012) revealed different values of water consumption (3.3e221 l/kg LWG). Thus, these authors state that the meat production in the pasture has no significant impact on water use, suggesting that the supposed contribution of livestock production to the water scarcity worldwide is unfounded.…”
Section: Resource Depletionssupporting
confidence: 85%
“…With a similar order to that found in the present study (95 and 217 l/kg LWG), the analysis of six systems for meat production in New South Wales, Australia, by Ridoutt et al (2012) revealed different values of water consumption (3.3e221 l/kg LWG). Thus, these authors state that the meat production in the pasture has no significant impact on water use, suggesting that the supposed contribution of livestock production to the water scarcity worldwide is unfounded.…”
Section: Resource Depletionssupporting
confidence: 85%
“…With water footprinting, geographical definition of water use is critical because of the variation in local water stress and therefore variation in the environmental impacts of water use. It was found that the water footprint varied substantially, from 3.3 to 221 L H 2 Oe (equivalent; [18]) per kg live weight at farm gate [16]. These results can be compared to other published results; for example, fresh milk produced in a low water stress region of Victoria, Australia (1.…”
Section: Introductionmentioning
confidence: 69%
“…The agriculture and food sectors are highlighted because they account for around 70% of global freshwater withdrawals [10] and are a major source of emissions responsible for freshwater quality degradation. This has led to the emergence of product water footprints as another stand-alone LCA-based environmental indicator [11], used especially in relation to food products [12][13][14][15][16][17][18][19], bio-fuels [20][21][22] and other water-intensive industry sectors such as electricity generation [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have calculated the water footprint of a wide variety of agricultural products such as cotton (Chapagain et al, 2006), rice , wheat (Mekonnen & Hoekstra, 2010), mango fruit (Ridoutt et al, 2010), tea and coffee (Chapagain & Hoekstra, 2007), meat and derivates (Ridoutt et al, 2012), olives and olive oil (Salmoral et al, 2011) and fresh tomatoes (Page et al, 2011). Most of these studies have estimated the volume of grey water for fertilizers, especially nitrogen and phosphorus, ignoring the potential contamination by applied pesticides, resulting in an underestimation of the volume of grey water.…”
Section: Introductionmentioning
confidence: 99%